GAMBARAN KESEHATAN MENTAL MAHASISWA TINGKAT AKHIR ANGKATAN 2021 FKIP UNIBA BANYUWANGI - Prasetyo, Fajar Wahyu; Napisah, Siti; Wulandari, Ratna; Putri, Desi Yunita (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This study aims to see the picture of mental health of final year students of the 2021 FKIP Uniba Banyuwangi class. The number of respondents in the study was 72. Students' mental health is seen from the aspects of psychological well-being and psychological stress. The results of the study showed that students' psychological well-being was in the very high category of 8.33%, high 38.88%, moderate 23.16%, low 26.38%, and very low 2.77%. The aspect of psychological stress was 15.27% very high, 18.05% high, 19.44% moderate, 25% low, and 22.22% very low. The mental health of male students was better than that of female students. The psychological well-being of male students was 56.25% high and psychological stress was 56.26% low. The psychological well-being of female students was 33.92% high and psychological stress was 14.28% low. Improvement of mental health needs to be done for further research.